2015
DOI: 10.17523/bia.v72n2p148
|View full text |Cite
|
Sign up to set email alerts
|

Estudo sobre o padrão de consumo da carne bovina na cidade de Campo Grande, MS, Brasil

Abstract: RESUMO: Objetivou-se identificar os padrões de consumo da carne bovina comparada ao consumo de carnes de frango, suíno, pescado e ovina. Os dados foram coletados por meio de questionários, junto à população da cidade de Campo Grande, MS, Brasil. Foram incluídos fatores sociais, educacionais, econômicos e específicos do consumo da carne bovina em relação à ordem de consumo, atributos da carne e preferência para o consumo. A pesquisa foi realizada com 429 consumidores, abordados na entrada de supermercados. Noto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
20

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 8 publications
1
3
0
20
Order By: Relevance
“…The educational level of the participant was mainly high school level, similar results have been compiled by (Dias et al (2015); Pinheiro et al (2010)) and Kirinus et al (2013) in other regions of Brazil.…”
Section: Characterization Of Participantssupporting
confidence: 84%
See 1 more Smart Citation
“…The educational level of the participant was mainly high school level, similar results have been compiled by (Dias et al (2015); Pinheiro et al (2010)) and Kirinus et al (2013) in other regions of Brazil.…”
Section: Characterization Of Participantssupporting
confidence: 84%
“…According to data from the Brazilian Institute of Geography and Statistics (IBGE) in relation to per capita household income, the average value of Brazil's income is USD 350. Pinheiro, Gomes, and Lopes (2010), Kirinus, Fruet, Klinger, Dörr, and Nörnberg (2013) and Dias et al (2015) also observed that the family income from different regions of Brazil (South, Midwest and North) ranges from 1 to 3 salaries. However, in this study the family income was higher (between 2 and 6 salaries) than the average observed for the rest of Brazil.…”
Section: Characterization Of Participantsmentioning
confidence: 91%
“…O atributo mais importante na decisão de compra da carne bovina em Dracena é a aparência da carne. Em Campo Grande-MS, a aparência/cor é o terceiro atributo mais importante entre 11 atributos estudados (Dias et al, 2015). A aparência de produtos perecíveis, como a carne bovina, dá a primeira impressão sobre a qualidade do produto no local de compra e afeta a expectativa sobre o sabor do alimento.…”
Section: Preferência Média Dos Consumidoresunclassified
“…Naturalmente, as empresas que aderirem a estes programas esperam obter uma compensação via mercado, através de diferenciação de preços. A textura (maciez e suculência) foi avaliada como um atributo muito importante na decisão de compras dos consumidores de Campo Grande-MS (Dias et al, 2015), Marília-SP (Oshiiwa et al, 2017) e Distrito Federal (Brisola & Castro, 2005).…”
Section: Introductionunclassified
“…In Porto Alegre (Brazil), appearance, price and the type of meat cut have the greatest importance to consumers at purchase time (GIACOMAZZI, 2016). In Campo Grande (Brazil), the most and the second most important attributes are hygienic conditions and good smell and appearance is the third most important beef attribute to consumers (DIAS et al, 2015).…”
Section: 2) Average Preferencementioning
confidence: 99%